Describing Aesthetic Experience: Creating a Model - Fairchild, Andrea (Canadian Journal of Education/Revue canadienne de l’éducation, 1991)
As part of a large research project on visitors’ response to and benefits from museum experiences, this study considered different paradigms of aesthetic experience. Applying various models, it analyzed transcripts of adults’ remarks during their visit to a fine arts museum. Three of the models are empirical, and two come from a developmental perspective. Research shows that age and exposure to art are significant factors in aesthetic response. A fourth, theoretical model charts individuals’ sequences of responses. Having assessed these models, I propose an alternative model that incorporates some features of the theoretical model into the empirically constructed ones. S’inscrivant dans une vaste recherche sur la réaction des visiteurs à des expé- riences muséales et les avantages qu’ils en retirent, cette étude a porté sur divers paradigmes d’expérience esthétique. À l’aide de divers modèles, j’ai analysé les propos d’adultes en visite dans un musée des beaux-arts. Trois des modèles sont empiriques et deux sont issus d’une perspective développementale. La recherche démontre que l’âge et les contacts avec l’art jouent un rôle important dans la réponse esthétique. Un quatrième modèle, théorique, permet d’établir les séquences de réponses des visiteurs. Après avoir évalué ces modèles, j’en propose un autre, qui intègre certaines caractéristiques du modèle théorique.